Pharmacokinetics of Esomeprazole in Oryctolagus Cuniculus Male Rabbit with Immobilized Stress - Neupane, Dr. Harish Chandra (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTIt has been reported that emotional stress influenced the drug absorption by inhibit the intestinal propulsion activity. Emotional stress is closely related to the pathogenesis of gastric ulcers. The effect of emotional stress on pharmacokinetics of antiulcer drug has not been conducted yet. Hence the present study aimed to investigate the effect of immobilization stress on pharmacokinetics of esomeprazole (gastric proton inhibitor) in Oryctolagus cuniculus male rabbits. Results showed that AUCinf, Cmax, Vz, and CL values determined without immobilized stress were higher than those determined using the immobilized stress. The bioavailability of esomeprazole without immobilized stress was found to be 85.33Â±21.23% which is higher than immobilized stress 61.33Â±19.45%, and was 1.39 fold difference(p=0.0051, P<0.05 . In Conclusion, Stress, in any form, can alter pharmacokinetic parameters, and thus, it is important that stress be minimized to obtained reliable pharmacokinetic data. The present study demonstrates that the immobilized stress can alters pharmacokinetics parameters significantly.